Pyrimethamine Elicits Antitumor Effects on Prostate Cancer by Inhibiting the p38-NF-κB Pathway - Zhou, Xumin; Zhang, Jinming; Hu, Xiaoping; He, Peiqing; Guo, Jianyu; Li, Jun; Lan, Tian; Liu, Jumei; Peng, Lilan; Li, Hua (Frontiers in Pharmacology, 2020)
Since incurable castration-resistant prostate cancer (CRPC) inevitably develops following treatment with androgen deprivation therapy, there is an urgent need to devise new therapeutic strategies to treat this cancer. Pyrimethamine, an FDA-approved anti-malarial drug, is known to exert an anti-tumor activity in various types of human cancer cells. However, whether pyrimethamine can inhibit prostate cancer is not well established. Hence, the present study aimed to characterize the mechanism of action of pyrimethamine on the prostate cancer. We investigated the potential effect of pyrimethamine on cell proliferation, cell cycle, and apoptosis in metastatic DU145 and PC3 prostate cancer cells. We found that pyrimethamine inhibited cell proliferation, induced cell cycle arrest in the S phase, and promoted cell apoptosis of prostate cells in vitro; it also suppressed tumor growth in xenograft models. In addition, we observed that pyrimethamine suppressed prostate cancer growth by inhibiting the p38-NF-κB axis in vitro and in vivo. Thus, this study demonstrates that pyrimethamine is a novel p38 inhibitor that can exert anti-proliferative and pro-apoptotic effects in prostate cancer by affecting cell cycle and intrinsic apoptotic signaling, thereby providing a novel strategy for using pyrimethamine in CRPC treatment.